Characteristics of delirium and its association with sedation and in-hospital mortality in patients with COVID-19 on veno-venous extracorporeal membrane oxygenation - Sun, Philip Young-woo; Fanning, Jonathon; Peeler, Anna; Shou, Benjamin; Lindsley, John; Caturegli, Giorgio; Whitman, Glenn; Cha, Stephanie; Kim, Bo Soo; Cho, Sung-Min, HERALD investigators (Frontiers in Medicine, 2023)
Background Veno-venous extracorporeal membrane oxygenation (VV-ECMO) has been used in patients with COVID-19 acute respiratory distress syndrome (ARDS). We aim to assess the characteristics of delirium and describe its association with sedation and in-hospital mortality. Methods We retrospectively reviewed adult patients on VV-ECMO for severe COVID-19 ARDS in the Johns Hopkins Hospital ECMO registry in 2020–2021. Delirium was assessed by the Confusion Assessment Method for the ICU (CAM-ICU) when patients scored−3 or above on the Richmond Agitation-Sedation Scale (RASS). Primary outcomes were delirium prevalence and duration in the proportion of days on VV-ECMO. Results Of 47 patients (median age = 51), 6 were in a persistent coma and 40 of the remaining 41 patients (98%) had ICU delirium. Delirium in the survivors (n = 21) and non-survivors (n = 26) was first detected at a similar time point (VV-ECMO day 9.5(5,14) vs. 8.5(5,21), p = 0.56) with similar total delirium days on VV-ECMO (9.5[3.3, 16.8] vs. 9.0[4.3, 28.3] days, p = 0.43). Non-survivors had numerically lower RASS scores on VV-ECMO days (−3.72[−4.42, −2.96] vs. −3.10[−3.91, −2.21], p = 0.06) and significantly prolonged delirium-unassessable days on VV-ECMO with a RASS of −4/−5 (23.0[16.3, 38.3] vs. 17.0(6,23), p = 0.03), and total VV-ECMO days (44.5[20.5, 74.3] vs. 27.0[21, 38], p = 0.04). The proportion of delirium-present days correlated with RASS (r = 0.64, p < 0.001), the proportions of days on VV-ECMO with a neuromuscular blocker (r = −0.59, p = 0.001), and with delirium-unassessable exams (r = −0.69, p < 0.001) but not with overall ECMO duration (r = 0.01, p = 0.96). The average daily dosage of delirium-related medications on ECMO days did not differ significantly. On an exploratory multivariable logistic regression, the proportion of delirium days was not associated with mortality. Conclusion Longer duration of delirium was associated with lighter sedation and shorter paralysis, but it did not discern in-hospital mortality. Future studies should evaluate analgosedation and paralytic strategies to optimize delirium, sedation level, and outcomes.